Asymmetric Reduction of Monoketo Hexadecanoic Acid Methyl Esters - Türker, Gülen; Yusufoglu, Ayse (Asian Journal of Chemistry, 2012)
Methyl 2-,3-,6-,8-,14- and 15-keto hexadecanoates were reduced by using NaBH4 in presence of 1,2;5,6-di-O-isopropilydene-D-glucofuranose [DIPGH], R(+)-1,1'-binaphthyl-2,2'-diol [RBND] and pivalic acid [PA]. The reduction of 2- and 3-keto esters in the presence of (+)-1,1'-binaphthyl-2,2'-diol results in considerably higher stereoselectivities (95 % ee). Enantiometric excess (ee %) was determined by 1H and 13C NMR analyses using a shift reagent, Eu(tfc)3.